Effect Of Soil And Microbiota Composition In Black Morel Continuous And Non-Continuous Cultures - Zhang, Yan (2024)
The black morel Morchella sextelata (Morchellaceae, Pezizales) is a valuable edible mushroom cultivated on a large scale, but severe yield decline occurs during continuous cropping. The effects of long-term cropping on soil properties, microbiome imbalances, and their impact on morel yield remain unclear. To help fill this knowledge gap, this study employed an indoor experiment to assess how cropping regimes affect soil properties, microbial communities, and morel production. This study assessed the impact of non-continuous cropping (NCC) and continuous cropping (CC) systems at three developing stages of M. sextelata development (bulk soil, conidial, and primordial stage) by using rDNA metabarcoding and network analysis. CC significantly reduced morel primordia yield in the third year compared to NCC, with the former showing a 99.7% reduction. The results showed that during the first year, M. sextelata mycelium overwhelmed the resident soil fungal community by reducing the alpha diversity and niche breadth of soil fungal patterns to a greater content compared to the continuous cropping regime, leading to high crop yield, but less complex soil mycobiome. To sustain continuous cropping, exogenous nutrition bags and morel mycelial spawn were consecutively added to the soil. The additional nutrient input stimulated the growth of fungal saprotrophic decomposers.